A Study on Issues and Challenges of Land Acquisition: With Special Reference to Women in Meerut District of Uttar Pradesh - Prof. Yudhvir Singh; Prof. Archna Singh (International Journal of Engineering and Management Research, 2024)
India is a developing country where continuous efforts are being made for industrialization and infrastructure development. Many capital investment projects have been taken up here for infrastructure development, which requires large parts of undeveloped land. The government fulfilled this requirement by the process of land Acquisition. The process of land acquisition has both positive and negative effects on the land owners and the women of their families. This paper studied the effects of land acquisition related to women empowerment in the Meerut District of Uttar Pradesh. This study has shown the property rights and distribution among women of land owners’ families, whose family lost their land in the process of land acquisition.